2021
DOI: 10.3389/fevo.2020.595614
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Termite Pheromones: Multifaceted, Context-Dependent, and Rational Chemical Communications

Abstract: Termite colonies, composed of large numbers of siblings, develop an important caste-based division of labor; individuals in these societies interact via intra- or intercaste chemical communications. For more than 50 years, termites have been known to use a variety of pheromones to perform tasks necessary for maintenance of their societies, similar to eusocial hymenopterans. Although trail-following pheromones have been chemically identified in various termites, other types of pheromones have not been elucidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 141 publications
0
21
0
Order By: Relevance
“…In neoisopteran termites, including R. speratus, only females have strong sex-pairing pheromones. In contrast, there is no such sex difference in basal lineages, with both sexes emitting pairing pheromones in some species and both sexes lacking them in others (14,37). Our results, therefore, emphasize that the assumptions of recent models for the evolution of SSB via indiscriminate mate choice (8) are not always met: same-sex pairing in termites occurs even with strong sex discrimination.…”
Section: Discussionmentioning
confidence: 46%
“…In neoisopteran termites, including R. speratus, only females have strong sex-pairing pheromones. In contrast, there is no such sex difference in basal lineages, with both sexes emitting pairing pheromones in some species and both sexes lacking them in others (14,37). Our results, therefore, emphasize that the assumptions of recent models for the evolution of SSB via indiscriminate mate choice (8) are not always met: same-sex pairing in termites occurs even with strong sex discrimination.…”
Section: Discussionmentioning
confidence: 46%
“…This study demonstrated that R. speratus uses a queen-speci c CHC pro le as a queen recognition pheromone to trigger aggregation of the workers, and suggests that R. speratus queens use both volatile compounds (as shown in Matsuura et al 2010) and non-volatile compounds as a signal to indicate the presence of the queen. Our study ndings strongly suggest that termites and social hymenopterans independently evolved the use of multicomponent queen signals by parsimonious use of CHCs for other purposes, enabling them to perform multifunctional roles (Le Conte et al 2008;Matsuura 2012;Leonhardt et al 2016;Hefetz 2019;Mitaka and Akino 2021). On the other hand, it is still unclear how AQS termites recognize the presence of a primary king in a colony because our GC-MS analysis did not detect any king-speci c or king-biased compounds (Tables S1 and S2 in the Electronic Supplementary Material).…”
Section: Discussionmentioning
confidence: 61%
“…3). In this clade, only females have sex-pairing pheromones, while in basal lineages, both females and males emit pairing pheromones [22,39]. Thus, the evolution of sexually dimorphic behaviour in tandems is clearly associated with the evolution of sex-specific signals, strongly arguing against a “mistaken identity” hypothesis of same-sex pairing in termites.…”
Section: Discussionmentioning
confidence: 99%